2018
DOI: 10.21323/2618-9771-2018-1-3-27-32
|View full text |Cite
|
Sign up to set email alerts
|

THE PROPERTIES OF THE CONIDIA OF STRAINS OF THE ACTINOMYCETE <i>STREPTOMYCES LUCENSIS</i> AND <i>STREPTOMYCES VIOLACEUS</i> DURING STORAGE AT LOW TEMPERATURES

Abstract: Collection cultures of actinomycetes are mainly stored in a dried state on adsorbents. Practiced low-temperature storage of actinomycetes at minus 70°C. The article presents the results of investigations of the properties of the conidia of strains of the actinomycete Streptomyces lucensis VKPM Ac–1743 and Streptomyces violaceus VKPM Ac–1734 is in the process of storage at minus 12°C and minus 18°C in glycerin solution and in 0,9 % aqueous sodium chloride solution. It was found that the inhibitory activity in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The collection of microorganisms of the All-Russian Research Institute of Food Additives (VNIIPD) contains the Streptomyces lucensis VKPM Ac-1743 and Streptomyces violaceus VKPM Ac-1734 strains -producers of glycosidase inhibitors, which are biologically active substances and potential food micro-ingredients [8]. Earlier studies have shown that during short-term storage for 30 days at a low temperature of 12 °C, the strains retained their viability and inhibitory activity [9].…”
Section: Introductionmentioning
confidence: 99%
“…The collection of microorganisms of the All-Russian Research Institute of Food Additives (VNIIPD) contains the Streptomyces lucensis VKPM Ac-1743 and Streptomyces violaceus VKPM Ac-1734 strains -producers of glycosidase inhibitors, which are biologically active substances and potential food micro-ingredients [8]. Earlier studies have shown that during short-term storage for 30 days at a low temperature of 12 °C, the strains retained their viability and inhibitory activity [9].…”
Section: Introductionmentioning
confidence: 99%